Into the woods - Paradis-Grenouillet, Sandrine; Aspe, Chantal; Burri, Sylvain (éditions Quae, 2018)
At the centre of concerns related to curbing the decline in forest biodiversity caused by increasing anthropogenic pressure and global change, old-growth forests are mainly characterised by the continuity of their tree cover. This has been defined mainly by their appearance on historical maps and by ecological criteria dating back to certain temporal cut-off points (about two centuries). Inherited over hundreds, even thousands, of years of interaction between Man and Nature, these ancient forests have been managed and shaped by past societies to meet their various needs, both domestic and industrial. Also, studying the historical trajectories of such forests, their responses to environmental and anthropogenic stress, and the long-term consequences of past human activities, is essential in order to better understand their current ecology and rethink their conservation. The development of pluridisciplinary and interdisciplinary research (ecology, paleoecology, history, archaeology, geography, sociology) now makes it possible not only to push back the hitherto accepted thresholds of ancientness, but in particular to understand old forests in their entirety and complexity over the longer term. This book, comprising both theoretical and methodological contributions along with case studies, reflects the diversity of current approaches and thinking and promotes interdisciplinarity as the only route to a comprehensive understanding of ancient forests as natural and cultural assets.